2017
DOI: 10.1080/15568318.2017.1292374
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of formal and informal institutions between local and regional authorities when creating well-functioning public transport systems

Abstract: The interplay of formal and informal institutions between local and regional authorities when creating well-functioning public transport systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Previous research sometimes argues that "deliberative governance approaches" are part of the solution to coordination problems that stand in the way of establishing efficient public transport systems (e.g., McLeod et al, 2017). The potential disconnection between regional public transport and local land use planning is one such "hotspot" where previous research has suggested that regional and local authorities create integrated planning through dialog that produces agreements with no statutory status (e.g., Hrelja et al, 2017). This research on governance in public transport can be viewed as a subset of a broader body of transport research (e.g., Stead, 2016) that shares a similar analytical interest in what can be achieved through so-called "informal" or "soft" forms of governance (in such different empirical areas as port governance, e.g., Ng, Monios, & Zhang, 2018, and partnerships for delivering better bus services, e.g., Stanley & van de Velde, 2008) that inform and coordinate the actions of discrete organizations.…”
Section: What Practical Recommendations On How Tomentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research sometimes argues that "deliberative governance approaches" are part of the solution to coordination problems that stand in the way of establishing efficient public transport systems (e.g., McLeod et al, 2017). The potential disconnection between regional public transport and local land use planning is one such "hotspot" where previous research has suggested that regional and local authorities create integrated planning through dialog that produces agreements with no statutory status (e.g., Hrelja et al, 2017). This research on governance in public transport can be viewed as a subset of a broader body of transport research (e.g., Stead, 2016) that shares a similar analytical interest in what can be achieved through so-called "informal" or "soft" forms of governance (in such different empirical areas as port governance, e.g., Ng, Monios, & Zhang, 2018, and partnerships for delivering better bus services, e.g., Stanley & van de Velde, 2008) that inform and coordinate the actions of discrete organizations.…”
Section: What Practical Recommendations On How Tomentioning
confidence: 99%
“…To plan and implement efficient public transport therefore requires the need for the collective action of organizations with different responsibilities and driven by different rationalities (Olesen, 2014;Pettersson, 2018). Successful collaboration between several formal, discrete organizationseach with its own budget and area of responsibilityworking across organizational boundaries on shared priorities and implementation, is therefore critical (Hrelja, Monios, Rye, Isaksson, & Scholten, 2017;Meyer, Campbell, Leach, & Coogan, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to recognise the distinction between institutions and organisations; according to North (1990), institutions represent the rules of the game, while organisations are the players. Having said that, an informal institution can be more than just a vague cultural norm but rather a fairly accepted and used network structure (often exploited by formal organisations) that nonetheless has no formal constitution, definition or power, more broadly interpreted as governance not defined in law (Hrelja et al 2017). It is also important to remain cognisant that, while seeking stability, institutional forms are in constant flux (Jessop 2001).…”
Section: Institutions and Institutionalismsmentioning
confidence: 99%